Impact of the Manchester Glaucoma Enhanced Referral Scheme on NHS costs. Issue 1 (30th September 2019) - Forbes, Hannah; Sutton, Matt; Edgar, David F; Lawrenson, John; Spencer, Anne Fiona; Fenerty, Cecilia; Harper, Robert
Abstract : Objectives: Glaucoma filtering schemes such as the Manchester Glaucoma Enhanced Referral Scheme (GERS) aim to reduce the number of false positive cases referred to Hospital Eye Services. Such schemes can also have wider system benefits, as they may reduce waiting times for other patients. However, previous studies of the cost consequences and wider system benefits of glaucoma filtering schemes are inconclusive. We investigate the cost consequences of the Manchester GERS. Design: Observational study. Methods: A cost analysis from the perspective of the National Health Service (NHS) was conducted using audit data from the Manchester GERS. Results: 2405 patients passed through the Manchester GERS from April 2013 to November 2016. 53.3% were not referred on to Manchester Royal Eye Hospital (MREH). Assuming an average of 2.3 outpatient visits to MREH were avoided for each filtered patient, the scheme saved the NHS approximately £2.76 per patient passing through the scheme. Conclusion: Our results indicate that glaucoma filtering schemes have the potential to reduce false positive referrals and costs to the NHS.